An insight on management of odontogenic orbital infections: report of two cases - Sharma Ankit; Ingole Snehal; Deshpande Mohan; Ranadive Pallavi; Sharma Sneha; Chavan Ankush (EDP Sciences, 2021)
Odontogenic infections are common and very often spread to potential spaces of head and neck. The spread of such infection to adjacent maxillary sinuses or distant sites such as the orbits are a rare occurrence and may develop periorbital and orbital cellulitis. Unfortunately once orbital cellulitis and subsequently orbital abscess develops it can give rise to serious complications such as complete blindness or even more serious and life-threatening situations as cavernous sinus thrombosis, intracranial abscess or even death. Two cases are presented to demonstrate the differences between the two conditions and the necessary management in either case. This article provides an insight into the clinical behaviour of orbital infections of odontogenic origin with contemporary diagnostic and treatment modalities that will help in reducing morbidity and mortality associated with these conditions.